Bare carbon electrodes as simple and efficient sensors for the quantification of caffeine in commercial beverages. Issue 5 (2nd May 2018) - Redivo, Luca; Stredanský, Miroslav; De Angelis, Elisabetta; Navarini, Luciano; Resmini, Marina; Švorc, Ĺubomír
Abstract : Food quality control is a mandatory task in the food industry and relies on the availability of simple, cost-effective and stable sensing platforms. In the present work, the applicability of bare glassy carbon electrodes for routine analysis of food samples was evaluated as a valid alternative to chromatographic techniques, using caffeine as test analyte. A number of experimental parameters were optimized and a differential pulse voltammetry was applied for quantification experiments. The detection limit was found to be 2 × 10 −5  M (3σ criterion) and repeatability was evaluated by the relative standard deviation of 4.5%. The influence of sugars, and compounds structurally related to caffeine on the current response of caffeine was evaluated and found to have no significant influence on the electrode performance. The suitability of bare carbon electrodes for routine analysis was successfully demonstrated by quantifying caffeine content in seven commercially available drinks and the results were validated using a standard ultra-high performance liquid chromatography method. This work demonstrates that bare glassy carbon electrodes are a simple, reliable and cost-effective platform for rapid analysis of targets such as caffeine in commercial products and they represent therefore a competitive alternative to the existing analytical methodologies for routine food analysis.